The cytoskeletal architecture of the presynaptic terminal and molecular structure of synapsin 1 (The Rockefeller University Press, 1989)
We have examined the cytoskeletal architecture and its relationship with synaptic vesicles in synapses by quick-freeze deep-etch electron microscopy (QF.DE). The main cytoskeletal elements in the presynaptic terminals (neuromuscular junction, electric organ, and cerebellar cortex) were actin filaments and microtubules. The actin filaments formed a network and frequently were associated closely with the presynaptic plasma membranes and active zones. Short, linking strands approximately 30 nm long were found between actin and synaptic vesicles, between microtubules and synaptic vesicles. Fine strands (30- 60 nm) were also found between synaptic vesicles. Frequently spherical structures existed in the middle of the strands between synaptic vesicles. Another kind of strand (approximately 100 nm long, thinner than the actin filaments) between synaptic vesicles and plasma membranes was also observed. We have examined the molecular structure of synapsin 1 and its relationship with actin filaments, microtubules, and synaptic vesicles in vitro using the low angle rotary shadowing technique and QF.DE. The synapsin 1, approximately 47 nm long, was composed of a head (approximately 14 nm diam) and a tail (approximately 33 nm long), having a tadpole-like appearance. The high resolution provided by QF.DE revealed that a single synapsin 1 cross-linked actin filaments and linked actin filaments with synaptic vesicles, forming approximately 30-nm short strands. The head was on the actin and the tail was attached to the synaptic vesicle or actin filament. Microtubules were also cross-linked by a single synapsin 1, which also connected a microtubule to synaptic vesicles, forming approximately 30 nm strands. The spherical head was on the microtubules and the tail was attached to the synaptic vesicles or to microtubules. Synaptic vesicles incubated with synapsin 1 were linked with each other via fine short fibrils and frequently we identified spherical structures from which two or three fibril radiated and cross-linked synaptic vesicles. We have examined the localization of synapsin 1 using ultracryomicrotomy and colloidal gold-immunocytochemistry of anti-synapsin 1 IgG. Synapsin 1 was exclusively localized in the regions occupied by synaptic vesicles. Statistical analyses indicated that synapsin 1 is located mostly at least approximately 30 nm away from the presynaptic membrane. These data derived via three different approaches suggest that synapsin 1 could be a main element of short linkages between actin filaments and synaptic vesicles, and between microtubules and synaptic vesicles, and between synaptic vesicles in the nerve terminals.(ABSTRACT TRUNCATED AT 400 WORDS)